Quadrature transmit array design using single-feed circularly polarized patch antenna for parallel transmission in MR imaging - Pang, Yong; Yu, Baiying; Vigneron, Daniel B.; Zhang, Xiaoliang (Quantitative Imaging in Medicine and Surgery; Vol 4, No 1 (February 25, 2014): Quantitative Imaging in Medicine and Surgery (Parallel and sparse MR imaging: methods and instruments——Part 1), 2014)
Quadrature coils are often desired in MR applications because they can improve MR sensitivity and also reduce excitation power. In this work, we propose, for the first time, a quadrature array design strategy for parallel transmission at 298 MHz using single-feed circularly polarized (CP) patch antenna technique. Each array element is a nearly square ring microstrip antenna and is fed at a point on the diagonal of the antenna to generate quadrature magnetic fields. Compared with conventional quadrature coils, the single-feed structure is much simple and compact, making the quadrature coil array design practical. Numerical simulations demonstrate that the decoupling between elements is better than –35 dB for all the elements and the RF fields are homogeneous with deep penetration and quadrature behavior in the area of interest. Bloch equation simulation is also performed to simulate the excitation procedure by using an 8-element quadrature planar patch array to demonstrate its feasibility in parallel transmission at the ultrahigh field of 7 Tesla.